Wisdom of Crowds: The Value of Stock Opinions Transmitted Through Social Media - Chen, Hailiang; De, Prabuddha; Hu, Yu (Jeffrey); Hwang, Byoung-Hyoun (Review of Financial Studies, 2014)
Social media has become a popular venue for individuals to share the results of their own analysis on financial securities. This paper investigates the extent to which investor opinions transmitted through social media predict future stock returns and earnings surprises. We conduct textual analysis of articles published on one of the most popular social media platforms for investors in the United States. We also consider the readers' perspective as inferred via commentaries written in response to these articles. We find that the views expressed in both articles and commentaries predict future stock returns and earnings surprises.